Optimation on Addition of Maize Sprout Extract to Improve the Quality and Taste of Soyghurt Intended for Dietetic Food of Ones with Coronary Heart Disease - Sukardi, Sukardi; Patulungan, M. Hindun; Purwaningsih, Isti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2001)
The aim of the experiment is to determine the optimal level of addition of maize sprout extract to improve the nutritional and the sensory characteristics of soyghurt intended for dietetic food of ones with coronary heart diseases. The experiment is carried out in a completely randomized design. Six levels of maize sprout extract i.e. 0 %, 10 %, 20 %, 30 %, 40 % and 50 % respectively, were added to soymilk. Parameters observed include fat, protein, N-amino content, protein quality (Protein Score and % Net Dietary Protein Efficiency), and the sensory characteristic, viscosity, taste, aroma and color of the soyghurt produced. The result showed that an addition of maize sprout extract at a level of 30 % to soymilk is found to be an optimum one to produce good quality soyghurt. It will reduce the fat content from 1.43 % to 0.82 %, but increase the level of unsaturated fatty acid of the soyghurt. It also result in the reduction of the protein of the formula from 5.67 % to 4.44 % and increase of N-amino from 1120 ppm to 1290 ppm. The improved formula soyghurt contains 0.82 % fat, 4.44 % protein, 1290 ppm N-amino, 51.98 Protein Score and Net Dietary Protein Efficiency of 7.25 %, and it is still considered to be acceptable in terms of viscosity, taste, aroma and color. Keywords: soyghurt, maize sprout, dietetic food